Gene discovery and molecular marker development, based on high-throughput transcript sequencing of Paspalum dilatatum Poir - Giordano, Andrea (2014)
Fil: Schrauf, Gustavo Enrique. Universidad de Buenos Aires. Facultad de Agronomía. Buenos Aires, Argentina.